Geography Plays a More Important Role than Soil Composition on Structuring Genetic Variation of Pseudometallophyte Commelina communis - Li, Jiaokun; Xu, Hui; Song, Yunpeng; Tang, Lulu; Gong, Yanbing; Yu, Runlan; Shen, Li; Wu, Xueling; Liu, Yuandong; Zeng, Weimin (Frontiers in Plant Science, 2016)
Pseudometallophytes are excellent models to study microevolution and local adaptation to soil pollution, as they can grow both on metalliferous and contrasting non-metalliferous soils. Although there has been accumulating evidence for the effects of edaphic conditions and geographical isolation on the genetic structure of pesudometallophytes, it is still a difficult problem in evolutionary biology to assess their relative importance. In this study, we investigated the spatial patterns of genetic variability, population differentiation and genetic groups in pseudometallophyte Commelina communis with 12 microsatellite loci. Eight metallicolous and six non-metallicolous populations of C. communis were sampled from cupriferous sites and surrounding non-contaminated areas in China. Neither significant reduction in genetic diversity nor apparent founder and bottleneck effects were observed in metallicolous populations of C. communis. Based on Bayesian and Neighbor-Joining clustering analyses and a principal coordinates analysis (PCoA), all sampled populations were found to be mainly separated into three genetic groups, corresponding well to their geographical locations rather than edaphic origins. Moreover, a significant and strong correlation between population genetic divergence and geographical distance were detected by Mantel test (r = 0.33; P < 0.05) and multiple matrix regression with randomization (MMRR; βD = 0.57, P < 0.01). However, the effect of copper concentration on genetic patterns of C. communis was not significant (MMRR; βE = -0.17, P = 0.12). Our study clearly demonstrated that the extreme edaphic conditions in metalliferous areas had limited effects on the genetic variability in C. communis. Geographic distance played a more important role in affecting the genetic structure of C. communis than soil composition did. In C. communis, the geographically disjunctive populations on metalliferous soils had multiple origins and evolved independently from nearby non-metallicolous populations.